Microalbuminuria In Diabetic Patients: Prevalence and Putative Risk Factors - Parchwani, Deepak; Singh, S. P.; Patel, Digisha (National Journal of Community Medicine, 2011)
Microalbuminuria refers to the excretion of albumin in the urine at a rate that exceeds normal limits but is less than the detection level for traditional dipstick methods and is considered as a marker of diabetic nephropathy. The current study was conducted to establish the prevalence of elevated urinary albumin levels (microalbuminuria) in a sequential sample of diabetic patients attending hospital diabetic clinics and to determine its relationship with known and putative risk factors, to identify micro- and normoalbuminuric patients in this sample for subsequent comparison of clinical characteristics of the micro- and normoalbuminuric patients identified and to ascertain relationship of serum angiotensin converting enzyme (ACE) activity with diabetic incipient nephropathy. This cross-sectional analytical study was conducted at Gujarat Adani Institute of Medical Sciences Bhuj (Gujarat). Patients having clinical albuminuria and with other causes of proteinuria were excluded. Data was analyzed by SPSS software. Microalbuminuria was observed in 34.48% in patients with type 1 and 28.33% in patients with type 2 diabetes mellitus respectively. There was no statistically significant difference in the frequency of microalbuminuria between type 1 and type 2 diabetes mellitus patients. Having the condition was significantly associated with advanced age, poor glycaemic control, dyslipidemia (with respect to total cholesterol, triglycerides and LDL-C), smoking, body mass index and coexisting hypertension. The duration of diabetes was a significant correlate in type 1 DM subjects only. No significant association with gender, HDL-C levels, age at onset of DM, mode of treatment, socio-economic status and other lifestyle variations was found. All clinical and biochemical parameters in patient with microalbuminuria was more adversely affected than patients with normoalbuminuria. Serum angiotensin converting enzyme (ACE) levels were significantly elevated (P<0.001) in both of the diabetic groups, moreover, its levels were higher in subjects with microalbuminuria than in those without this complication (P<0.05).